Control of isolated microgrid based renewable energy generation using PID controller - Regad Mohamed Sidi Brahim; M'hamed Helaimi; Rachid Taleb (International Journal of Applied Power Engineering (IJAPE), 2021)
This paper investigates optimal PID controller tuning using particle swarm optimization for frequency control in the microgrid system. The proposed microgrid composed of renewable sources such as wind turbine generation and solar system with diesel engine generator and storage systems such as the battery, flywheel, aqua electrolyze, and fuel cell. The microgrid based on renewable energy sources faces different challenges in operation and stability due to the stochastic nature of solar radiation and wind speed that depend upon the weather conditions. Among these challenges, the frequency and power deviations are affected by the sudden unbalance between generation and load which require a suitable and adequate regulation. The principal objective of this study is to reduce the frequency and power deviation by the use of the PID controller optimized based particle swarm optimization due to its simplicity and flexibility to overcome this kind of issues. The simulation results show the better performances and robustness of the proposed controller against the disturbances in load and generations in comparison to using a genetic algorithm.